The masterwork in music: Volume II - Schenker, Heinrich 1868-1935 (Cambridge Cambridge University Press, 1996)
The Masterwork in Music comprises the main writings from the mid-1920s to 1930 of the eminent Austrian theorist and music-philosopher, Heinrich Schenker (1868SH1935); these range from detailed analyses of individual works to discussions of music theory in a historical/cultural context to general thoughts about music, art and culture. The third and final volume of Masterwork embraces all three types of essay, but is in reality dominated by the most detailed and